Hermeneutika dalam Penafsiran Hukum Adat: Implikasi terhadap Hukum Ekonomi Syariah di Era Globalisasi - Hasanudin, Maulana; Sururie, Ramdani Wahyu; Rizkia, Nabila Subur; Muslim, Dendi Ramdani (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2025)
This article aims to analyze the role of hermeneutics in the interpretation of customary law and its implications for Sharia economic law in the era of globalization. This research contributes to revealing how hermeneutics can serve as an adaptive interpretative method to align customary law with the principles of Sharia economic law, ensuring its relevance in modern economic dynamics. This study is categorized as library research with a qualitative approach. The methodology used is a normative-juridical study. Hermeneutics in the interpretation of customary law functions as an interpretative method that ensures customary law remains relevant to social and economic developments without losing its identity. In the context of Sharia economic law in the era of globalization, hermeneutics enables the reinterpretation of customary law to align with Islamic economic principles, allowing it to adapt to the increasingly complex challenges of the global economic system.